2013
DOI: 10.1111/ped.12014
|View full text |Cite
|
Sign up to set email alerts
|

Severe gastric variceal bleeding successfully treated by emergency splenic artery embolization

Abstract: A 53-year-old male patient with a history of hepatocellular carcinoma developed gastroesophageal varices refractory to endoscopic injection sclerotherapy (EIS). He required EIS six times in 2 years for recurring variceal bleeding. After hepatic resection, he developed massive splenomegaly. Partial splenic embolization (PSE) was performed to reduce the portal pressure. Varices and variceal bleeding were not detected during 13-year follow up, until the patient died of hepatocellular carcinoma. This is a unique c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…Consistent with these studies, variceal bleeding in our study decreased significantly in all patients receiving TIPS. Despite PSE being reported as efficacious in reducing variceal bleeding [8] by reducing portal venous flow and pressure, combined therapy using TIPS and PSE in our study did not achieve significantly more reduced variceal bleeding compared to that of patients receiving TIPS alone, which might be related to the already very low bleeding frequencies obtained by creation of TIPS.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Consistent with these studies, variceal bleeding in our study decreased significantly in all patients receiving TIPS. Despite PSE being reported as efficacious in reducing variceal bleeding [8] by reducing portal venous flow and pressure, combined therapy using TIPS and PSE in our study did not achieve significantly more reduced variceal bleeding compared to that of patients receiving TIPS alone, which might be related to the already very low bleeding frequencies obtained by creation of TIPS.…”
Section: Discussioncontrasting
confidence: 88%
“…PSE was also carried out by the same interventional radiologists, according to the method described in previous studies [8,15] . During the procedure, a 5.0-F RH or Yashiro catheter (Terumo, Tokyo, Japan) was used to demonstrate the distribution of splenic arteries and collateral circulation routes, and spring coils(18-6/2mm, 18-10/4mm, Cook Inc., Bloomington, IN, USA) were used to embolize branches of the splenic arteries with a splenic infarction ratio set at below 50% ( Figure 2B).…”
Section: Pse Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Sankararaman et al planned to embolize 80~90% of the spleen. After selective SAE, huge area of spleen was infarcted [6]. In our case, we performed nonselective SAE; then only small portion of spleen was infarcted.…”
Section: Discussionmentioning
confidence: 92%
“…Some authors have reported that splenic artery embolization (SAE) is an effective alternative to splenectomy for the treatment of gastric variceal bleeding with left-sided portal hypertension [2, 5, 6]. …”
Section: Introductionmentioning
confidence: 99%